Perspectivas para uma formação culturalmente contextualizada de professores de música: problematizações, reflexões e propostas a partir da Licenciatura em Música da UFCG - Ferreira Filho, João Valter (2021)
This dissertation's primary goal is to understand how the Federal University of Campina Grande's Music Teacher Education Program proposal and the Program's cultural context have interacted themselves. This work also analyzes how this Program's reality might, from and articulated to the Program subjects' perceptions, conformations, and prepositions, subsidize proposals and perspectives toward a culturally responsive music teacher education in this undergraduate Program. The methodological approach is based on qualitative research, but procedures to collect and analyze quantitative data were also utilized. The study was conducted between 2017 and 2020 based on participant observation, focus group sessions, questionnaires application, memorials production, and semi-structured interviews with teachers, students, and former students from the Program. The data collection and organization procedures included: literature selection, categorization and analysis, interview transcriptions, focus groups debate transcriptions, discourse analysis, and data tabulation in graphs, charts, and tables. The theoretical pillars that support the dissertation show the need to think about the music teaches education process from a diversity of perspectives, considering, among other aspects, cultural context’s particularities, demands, and needs of each Program. The study has shown that the Music Teacher Education Program of UFCG is inserted in a context marked by popular culture's musicality, the expressive presence of music bands and religious groups, and different urban popular music expressions. However, the data also showed that, despite this scenario's musical diversity characteristic, the number of formal contexts for music teaching in the city and its surroundings is minimal. This feature represents a challenge for the professional insertion of the Program alumni. The research results also highlighted that the Educational Project address through its profile and objectives that the Program was expected to establish an effective dialogue between the teacher education process and the Program cultural context. However, the curricular structure presented in the document shows a classical-conservatory-training-based education process, which has little relation with the local, regional, and national cultural universe. On the one hand, the teacher, students, and alumni views often conform to this trend. However, they also point to the need for the Program to incorporate new dimensions and educational paths, especially concerning a more significant interrelationship with the cultural dimensions that make up students' and teachers' universe today. Based on all evidence from this research approach, this dissertation proposes alternatives to implementing a culturally responsive music teacher education for the Teacher Music Education Program of UFCG. This work concludes with perspectives such as the integration between knowledge, diversity, adherence to new modes of learning, engagement with music and the local professional scene, the protagonism of the Program subjects (students and professors), and commitment to ethics and social responsibility.